2010
DOI: 10.1590/s1516-14392010000100017
|View full text |Cite
|
Sign up to set email alerts
|

Post-irradiation vickers microhardness development of novel resin composites

Abstract: The aim of this study was to evaluate the effect of post-irradiation dry aging at different periods of time on Vickers microhardness of some dental composites based on various resin matrices. Sixty four disc-shaped specimens of the resin composites were prepared in a split Teflon mold (8 × 2 mm) and irradiated by Optilux 501 light cure (500 mW.cm -2 for 40 seconds) on their top side. The specimens were aged-dry in dark at 23 and 37 °C for the following storage periods; immediate, 1/2 an hour, 1, 6, 12, 24, 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…The high viscosity of pMEMO and the known lower reactivity of methacrylate groups in hybrid systems (due to mobility restrictions) are effects that can be improved with the addition of diluting monomer TEGDMA and making the reticulation process more effective. Previous studies reported an increase in Vickers hardness of resins formed by ORMOCER  /TEGDMA with an increase in the content of the diluting monomer, which is in agreement with the results found for the current experimental design 9 .…”
Section: Experimental Designsupporting
confidence: 92%
See 1 more Smart Citation
“…The high viscosity of pMEMO and the known lower reactivity of methacrylate groups in hybrid systems (due to mobility restrictions) are effects that can be improved with the addition of diluting monomer TEGDMA and making the reticulation process more effective. Previous studies reported an increase in Vickers hardness of resins formed by ORMOCER  /TEGDMA with an increase in the content of the diluting monomer, which is in agreement with the results found for the current experimental design 9 .…”
Section: Experimental Designsupporting
confidence: 92%
“…In hybrid resins, an inorganic three-dimension network is formed by polycondensation of the alkoxysilanes, producing siloxane bonds (Si-O-Si) as hard as those of glass, this may explain the high hardness of these materials. Studies have demonstrated that comparatively to dental restorative resins based on conventional dimethacrylate monomers, formulations containing organic-inorganic hybrid polymers have higher hardness values 9 . Pure organic-inorganic polymers are highly viscous, which makes their handling and consequently curing difficult 10 .…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45] Although all RBCs exhibit some postirradiation polymerization, the amount depends upon the RBC used and the extent to which it has been polymerized. 43,45 After 24 hours, the increase in hardness can range from 12% for a well-polymerized RBC to over 350% for the same RBC when it is less well polymerized.…”
Section: Introductionmentioning
confidence: 99%
“…There are discrepancies in outcomes of previous reports concerning the polymerization kinetics after light-curing of RBCs. Hansen 18 found that the most of the polymerization reaction takes place during the first minutes after irradiation or one hour after removal of the irradiation source, while Leung et al, 19 reported that a significant portion of reaction may occur during the first 24 h. Moreover, in a recent study it has been reported a further increase in microhardness of 50-80% of the immediate readings for some RBC materials in room temperature after 168 h 20 . The extent of post-irradiation polymerization may be influenced by various intrinsic factors such as monomer composition, availability of free radicals and initial degree of conversion.…”
mentioning
confidence: 98%